Densities, Viscosities, Refractive Indices and Sound Speeds of Acetophenone with Methylacetate at Different Temperatures. Issue 4 (2012) - Saravanakumar, K.; Baskaran, R.; Kubendran, T. R.
Abstract : Densities, viscosities, refractive indices and ultrasonic velocities of the binary mixtures of Acetophenone with Methyl acetate were measured over the entire mole fractions at (303.15, 313.15 and 323.15) K. From these experimental results, excess molar volumes V E, viscosity deviation ∆η, refractive index deviation ∆nD, deviations in isentropic compressibility ∆Ks and excess intermolecular free length ∆Lf are calculated. The viscosity values were fitted to the models of Krishnan-Laddha and McAllister. The thermo physical properties under study were fit to the Jouyban - Acree model. The excess values were correlated using Redlich-Kister polynomial equation to obtain their coefficients and standard deviations. It was found that in all cases, the data obtained fitted with the values correlated by the corresponding models very well. The results are interpreted in terms of molecular interactions occurring in the solution.